2021
DOI: 10.1177/09673911211046780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recovered brown alumina filler loading on mechanical, hygrothermal and thermal properties of glass fiber–reinforced epoxy polymer composite

Abstract: This study investigates the efficiency of recovered brown alumina (RBA) particles filled in epoxy glass-fiber composites. The RBA particles were obtained from grinding wheel rejects with the help of the mechanical crushing process. Recovered particles finer than 120 grit were used as particulate filler for composite preparation. Composites were processed through a hand-layup technique by varying RBA filler loading percentages (0, 5, 10, 15, and 20 wt.%) in a glass fiber–reinforced epoxy matrix. Physical, mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Marble powder dust addition to the polymer composites, improved the shore hardness, impact and compressive strengths and marginal drop in the tensile and flexural properties [13]. Inclusion of 20% of recovered alumina to polymer composite resulted in maximum hardness and flexural strength [33]. Many ceramic fillers like Al 2 O 3 , TiO 2 , MgO, SiO 2 are added to the polymer composite and its behavior was studied and found that, the additives enhanced the flexural properties, impact strength.…”
Section: Results and Findings Discussionmentioning
confidence: 99%
“…Marble powder dust addition to the polymer composites, improved the shore hardness, impact and compressive strengths and marginal drop in the tensile and flexural properties [13]. Inclusion of 20% of recovered alumina to polymer composite resulted in maximum hardness and flexural strength [33]. Many ceramic fillers like Al 2 O 3 , TiO 2 , MgO, SiO 2 are added to the polymer composite and its behavior was studied and found that, the additives enhanced the flexural properties, impact strength.…”
Section: Results and Findings Discussionmentioning
confidence: 99%
“…Reinforcement of fiber particulate can improve the composite's thermal stability, crystalline index, and mechanical performance (Azman et al, 2021). Various papers reported that particulate reinforcement could marginally improve compressive strength (Vinayagam, 2022), flexural strength (Sabarinathan et al, 2021), impact strength (Benin et al, 2022), ductility (Xiong et al, 2021), tensile strength (Cheang and Khor, 2003), wear (Aly et al, 2012), toughness (Bhagyashekar and Rao, 2010), scratch resistance (Ng et al, 2001), coefficient of thermal expansion (Sun et al, 2021;Xu et al, 2001), thermal conductivity (Bahl, 2020;Bae et al, 2000;Luyt et al, 2006), etc. Sawyer et al (2003 reported the beneficial use of glass particulate fiber to improve the corrosion and wear behavior of Polytetrafluoroethylene composite.…”
Section: Particulate Fiber Reinforced Composite (Pfrc)mentioning
confidence: 99%